Character Formation of Students Through the Song Ina Hai Ata Kiri at SDN 2 Lamahala Jaya, East Flores Regency, East Nusa Tenggara Province - Fadjar Noer Dzaman Putra Metha, Muh; Nirsantuni, Baiq; Subhan, Subhan; Agus Mega Saputra , Gde; Taufiqqurrahman (International Journal of Social Sciences and Humanities, 2025)
Character formation is a crucial aspect of education that can be achieved through various media, one of which is regional songs. Regional songs contain cultural, moral, and social values that can be transferred to elementary school students. Thus, the cultivation of character formation in students needs to be enhanced to create a better generation in line with Pancasila's spirit. One way to achieve this is through the use of the regional song Ina Hai Ata Kiri in character formation for students at SDN 2 Lamahala. The focus of this research is to understand how character formation is instilled through regional songs in cultural arts education at SDN 2 Lamahala and to assess students' achievements in implementing the regional song Ina Hai Ata Kiri, impacting their character formation. This research uses a descriptive qualitative approach, which provides descriptions and depictions of the learning activities involving the song Ina Hai Ata Kiri and the values embedded in it that shape students' characters. The results indicate that the process of learning the song Ina Hai Ata Kiri and character formation carried out in the lessons at SDN 2 Lamahala has been quite successful. This is evident from the observations and interviews conducted, showing that students' characters were shaped in terms of: cultural appreciation, honesty, religiosity, responsibility, unity, courage and confidence, hard work, cooperation, and care.